The VANDELS survey: a measurement of the average Lyman-continuum escape fraction of star-forming galaxies at z = 3.5. Issue 3 (19th April 2022) - Begley, R; Cullen, F; McLure, R J; Dunlop, J S; Hall, A; Carnall, A C; Hamadouche, M L; McLeod, D J; Amorín, R; Calabrò, A; Fontana, A; Fynbo, J P U; et al.
ABSTRACT: We present a study designed to measure the average Lyman-continuum escape fraction (〈 f esc 〉) of star-forming galaxies at z ≃ 3.5. We assemble a sample of 148 galaxies from the VANDELS spectroscopic survey at 3.35 ≤  z spec ≤ 3.95, selected to minimize line-of-sight contamination of their photometry. For this sample, we use ultra-deep, ground-based, U -band imaging and Hubble Space Telescope V -band imaging to robustly measure the distribution of $\mathcal {R_{\rm obs}}\, =(L_{\rm LyC}/L_{\rm UV})_{\rm obs}$ . We then model the $\mathcal {R_{\rm obs}}$ distribution as a function of 〈 f esc 〉, carefully accounting for attenuation by dust, the intergalactic medium and the circumgalactic medium. A maximum likelihood fit to the $\mathcal {R_{\rm obs}}$ distribution returns a best-fitting value of $\langle f_{\rm esc}\rangle =0.07^{+0.02}_{-0.02}$, a result confirmed using an alternative Bayesian inference technique (both techniques exclude 〈 f esc 〉 = 0.0 at >3σ). By splitting our sample in two, we find evidence that 〈 f esc 〉 is positively correlated with Ly α equivalent width ( W λ (Ly α)), with high and low W λ (Lyα) subsamples returning values of $\langle f_{\rm esc}\rangle =0.12^{+0.06}_{-0.04}$ and $\langle f_{\rm esc} \rangle =0.02^{+0.02}_{-0.01}$, respectively. In contrast, we find evidence that 〈 f esc 〉 is anticorrelated with intrinsic UV luminosity and UV dust attenuation; with low UV luminosity and dust attenuation subsamples both returning best fits in the range 0.10 ≤ 〈 f esc 〉 ≤ 0.22. We do not find a clear correlation between f esc and galaxy stellar mass, suggesting stellar mass is not a primary indicator of f esc . Although larger samples are needed to further explore these trends, our results suggest that it is entirely plausible that the low dust, low-metallicity galaxies found at z ≥ 6 will display the 〈 f esc 〉 ≥ 0.1 required to drive reionization.